2023
DOI: 10.1093/pcp/pcad142
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis CML13 and CML14 Have Essential and Overlapping Roles in Plant Development

Kyle Symonds,
Howard Teresinski,
Bryan Hau
et al.

Abstract: Calmodulin-like proteins (CaM-like; CML) are the largest family of calcium-binding proteins in plants, yet the functions of most CMLs are unknown. Arabidopsis CML13 and CML14 are closely related paralogs that interact with the isoleucine-glutamine (IQ) domains of myosins, IQ-domain (IQD) proteins, and CaM-activated transcription factors (CAMTAs). Here, we explored the physiological roles of CML13 and CML14 during development by using dexamethasone-inducible RNA silencing to suppress either CML13 or CML14 trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…We previously showed that suppression of CML13 or CML14 expression results in strong, aberrant phenotypes throughout development ( Symonds et al , 2023 ). An earlier report examined the phenotypes of myosin mutants and found that a myosin VIII mutant, atm1 , and myosin XI triple mutants (X1-1, -2, -K), xi3KO , exhibited reduced hypocotyl elongation relative to wild-type plants ( Olantunji and Kelly, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously showed that suppression of CML13 or CML14 expression results in strong, aberrant phenotypes throughout development ( Symonds et al , 2023 ). An earlier report examined the phenotypes of myosin mutants and found that a myosin VIII mutant, atm1 , and myosin XI triple mutants (X1-1, -2, -K), xi3KO , exhibited reduced hypocotyl elongation relative to wild-type plants ( Olantunji and Kelly, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In Arabidopsis, these putative targets represent 56 different proteins, each with multiple IQ domains, and thus, like CaM, the number and variety of cellular processes that CML13/14 may participate in is expansive. Both CML13 and CML14 are important in plant growth throughout development, as suppression of either leads to a pleiotropic phenotype ( Symonds et al , 2023 ). Moreover, CML13 and CML14 function in abiotic stress responses, and a recent report found that cml13 mutants exhibit enhanced germination under salinity stress ( Hau et al , 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations